Virtual Land: Deciphering Blockchain-Based Property Transactions and Their Legal Implications - Muhammad Asrul Maulana; Mochamad Tanzil Multazam (Jurnal Wawasan Yuridika, 2023)
This study aims to investigate the scheme of virtual land transactions based on blockchain technology and the legal relationships among parties involved in such transactions. This research is descriptive, with the type of normative juridical research, using statutory and conceptual approaches, data collection techniques in the form of literature studies, then the data are analyzed qualitatively. The results reveal that the transaction process on platforms like Decentraland and The Sandbox includes registering a digital wallet, purchasing virtual land, managing and developing the land, reselling it as an NFT asset, and exchanging cryptocurrencies for local currency. The legal relationships between sellers, buyers, and platform owners are also identified. This research contributes to users' understanding of virtual land transactions and intellectual property ownership in the digital realm.